Programa Flex Isquios en Primaria y Secundaria. - Merino-Marban, Rafael; López-Fernández, Iván (Universidad de Málaga, 2025)
The purpose of this study was to research the effect of a stretching program on hamstring flexibility in schoolchildren from Primary and Secondary Education. Methods. For practical reasons and the nature of the present study (i.e. intervention focused on natural groups in a school setting) a cluster-randomized controlled design was used. Balanced by school and grades, natural classes were assigned randomly to form one of the following study groups: warm-up group (WUG), cool-down group (CDG), mix group (MXG) and non-stretching group (NSG). A total of 289 Primary and 99 Secundary schoolchildren were divided into four groups. The 3 EGs performed hamstring stretches for 4 minutes during each Physical Education class over a two-month period, 2 sessions per week (8 weeks, for a total of 16 PE sessions), with a stretch duration of 20 seconds, utilizing the static passive technique. The EG1 performed the stretching exercises during warm-up (4 minutes), the EG2 performed the stretching exercises during cool-down (4 minutes) and finally the EG3 performed the stretching exercises during warm-up (2 minutes) and cool-down (2 minutes) period. The control group followed the standard class program of PE classes. Hamstring flexibility was measured using the PSLR, PKEA and BS-SR test in a random order before and after the program. Finally, after two weeks without performing stretching exercises, a new measurement was taken with the aim of observing the levels of retention. The statistical significance level was set at p < 0.05. All statistical analyses were performed using SPSS version 25.0 for Windows (IBM® SPSS® Statistics). Conclusion. This study indicates that incorporating a static passive stretching program as part of Physical Education classes increases the ROM of the hamstrings in schoolchildren.
Keywords: Músculos - Flexibilidad; Niños; Educación física para niños; Flexibility; Children; Intervention; Field test; Hamstring muscles extensibility